Management of Extracuricular Activities of Scouts in Improving The Quality Of Students at Madrasah Tsanawiyah (MTs) Negeri 4 Kebumen - Tursini Tursini (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2019)
This research is based on the importance of scout extracurricular activities in improve the quality of students. In this regard, this study aims to find out the management of scout extracurricular activities in improving quality students at Madrasah Tsanawiyah (MTs) Negeri 4 Kebumen. This research is qualitative research. Collecting data using interviews, observation, and documentation, and data validity using triangulation, and data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. This research produce the following conclusions. (1) Extracurricular Activity Planning Scouting in Improving the Quality of Students at MTs Negeri 4 Kebumen was carried out at the start of each new school year. Planning is carried out by the principal, deputy head student section of the school, vice principal of the curriculum section, activity coordinator extracurriculars, and mentor teachers. (2) Implementation of extracurricular activities at MTs Negeri 4 Kebumen is grouped into two, namely, compulsory extracurricular and elective extracurriculars. Compulsory extracurriculars are extra activities that must be attended by all grade 7 and grade 8 students. While extracurricular options include: volleyball, football, qiraah, drum band, and music arts. Extracurricular activities run every day the day after the completion of teaching and learning activities. The extracurricular activities are running smoothly, according to the schedule that has been prepared. (3) Evaluation of extracurricular activities in MTs Negeri 4 Kebumen is held every three months. Things that are evaluated include targets that have been set, such as the champion target the school wants to achieve, the number of meetings that must be fulfilled in one semester, student participation in extracurricular activities and the results of learning extracurricular activities. (4) Quality / quality of learners after holding the management of extracurricular activities at MTs Negeri 4 Kebumen relatively good and increasing. Judging from the ongoing educational process smoothly and got many non-academic achievements.